Failure Analysis of a Reactor after Explosion Accident. (2015) - Xue, X.L.; Tang, X.Y.; Lu, H.L.; Geng, X.F.
Abstract: Burst of a reactor occurred in an explosion accident during the production of antistatic agent process. According to the results of site survey, the current regulations and standards as well as the requirements of the accident investigation group, the reason of burst was discussed by failure analysis of the shell and bolts. The shell strength was analyzed by visual inspection, thickness measurement, and strength verification as well as estimating of bursting pressure. It can be concluded that the tank strength met the requirements of design condition. The bolts of the reactor was broken in the accident, so the failure analysis of bolts was carried out in detail, including visual inspection, fracture examination, chemical composition analysis, mechanical testing and strength verification. According to the results of the measured mechanical properties, the strength of the bolts was verified. It can be concluded that the bolts could bear the proof pressure test safely. Fracture analysis shows that no obvious metallurgical defects were found, the bolts were broken due to extreme overload. According to the technical analysis of the shell and the bolts, it can be concluded that the reactor could service safely under normal operating conditions. The cause of the bursting was transient extreme overpressure.